The Effect Of Transformational Leadership On Organizational Citizenship Behavior And Nurse Loyalty As Intrvenning Variable (Empirical Study of Medical Employees at RSIA EB) - Kasmiruddin, Kasmiruddin; Dailiati, Surya; Hernimawati, Hernimawati; Prihati, Prihati; Sputra, Trio (International Journal of Science, Technology & Management, 2022)
The complexity of the duties of nurses providing medical and non-medical services to patients in hospitals make the nurse must work spontaneously and voluntarily and ready to help the interests of the hospital even work beyond formal standards, this behavior is called organizational citizenship behavior (OCB). This study aimed to analyze the direct and indirect effect of transformational leadership on organizational citizenship behavior (OCB) through the Variable of nurse loyalty. The research population was all medical employees, especially nurses, totaling 75 people and all population units were used as research respondents. Research Variable were measured using a Likert scale with five categories and were collected using a questionnaire distribution. After the data were collected and analyzed with PLS version 21 analysis. From the results of the study it was found that the direct influence of transformational leadership on nurse OCB behavior was lower than the indirect effect, namely the Variable of nurse loyalty. It can be concluded that the RSIA EB must consider the effect of transformational leadership on increasing nurse loyalty, so that the effect on nurse OCB behavior is higher.